Household Food Insufficiency and Chronic Pain among Children in the US: A National Study - See Wan Tham; Emily F. Law; Tonya M. Palermo; Flavia P. Kapos; Jason A. Mendoza; Cornelius B. Groenewald (MDPI AG, 2023)
This study aimed to determine the prevalence of pediatric chronic pain by household food sufficiency status and examine whether food insufficiency would be associated with greater risk for chronic pain. We analyzed data from the 2019-2020 National Survey of Children's Health of 48,410 children (6-17 years) in the United States. Across the sample, 26.1% (95% CI: 25.2-27.0) experienced mild food insufficiency and 5.1% (95% CI: 4.6-5.7) moderate/severe food insufficiency. The prevalence of chronic pain was higher among children with mild (13.7%) and moderate/severe food insufficiency (20.6%) relative to children in food-sufficient households (6.7%, p < 0.001). After adjusting for a priori covariates (individual: age, sex, race/ethnicity, anxiety, depression, other health conditions, adverse childhood events; household: poverty, parent education, physical and mental health; community: region of residence), multivariable logistic regression revealed that children with mild food insufficiency had 1.6 times greater odds of having chronic pain (95% CI: 1.4-1.9, p < 0.0001) and those with moderate/severe food insufficiency, 1.9 higher odds (95% CI: 1.4-2.7, p < 0.0001) relative to food-sufficient children. The dose-response relationship between food insufficiency and childhood chronic pain highlights the importance of further research to identify underlying mechanisms and evaluate the impact of food insufficiency on the onset and persistence of chronic pain across the lifespan.